1997
DOI: 10.1002/(sici)1097-4547(19970115)47:2<186::aid-jnr7>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic steroids induce injury and apoptosis of differentiated skeletal muscle

Abstract: Apoptosis is an active form of cellular death, or suicide, which plays an important physiologic role during organ development and in cellular turnover in differentiated tissues. Apoptosis has also been demonstrated to occur in several organs in response to hypoxic/ischemic, oxidative, or drug-induced injury and is thus involved in disease pathogenesis. However, it is generally assumed that apoptosis does not occur in differentiated skeletal muscle. Apoptosis has been demonstrated in differentiated myocardial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…In these cases muscle pain was associated with rhabdomyolysis, however the development of renal failure was averted with supportive measures including optimisation of fluid balance and forced alkaline diuresis. Research using animal models has demonstrated that anabolic steroids induce apoptosis on differentiated skeletal model (9).…”
Section: Textmentioning
confidence: 81%
“…In these cases muscle pain was associated with rhabdomyolysis, however the development of renal failure was averted with supportive measures including optimisation of fluid balance and forced alkaline diuresis. Research using animal models has demonstrated that anabolic steroids induce apoptosis on differentiated skeletal model (9).…”
Section: Textmentioning
confidence: 81%
“…Neste contexto, AbuShakra e cols. (62) demonstraram que a exposição in vitro de células musculares diferenciadas (C2 murina) a doses supra-fisiológicas de EAA induziu apoptose, e que a diminuição da concentração de DNA nestas culturas foi proporcional à concentração de EAA utilizada. Resultados semelhantes foram obtidos após administração de EAA danazol (62).…”
Section: Gruposunclassified
“…necrotic, early-and late-apoptotic cells based on the method described by Abu-Shakra et al [1]. In ultraviolet light, one thousand nuclei in total were counted in ten (or more if necessary) randomly chosen visual fields per slide (if possible, since some treatments were accompanied by extensive cell detachment) and cells were qualified as follows: regular oval shaped blue nuclei (live cells); partially shrunk blue nuclei (early apoptotic) or condensed white-blue nuclei (late apoptotic); regular oval shaped or condensed pink nuclei (dead cells regardless of origin -apoptotic or necrotic).…”
Section: Determination Of Intracellular H 2 Omentioning
confidence: 99%